Interactive PowerPoint Media Oriented to Differentiated Learning Fraction Material for Mathematics Subjects for Grade IV Elementary School - Ni Komang Sri Rahayu; I Nyoman Laba Jayanta; Komang Sujendra Diputra (International Journal of Elementary Education, 2025)
Mathematics learning in fraction material for grade IV Elementary School often encounters obstacles, especially because students have different levels of readiness and learning styles. The lack of interactive and adaptive media is one of the causes of students' low understanding of the concept of fractions. This study aims to analyze the effectiveness of interactive PowerPoint media oriented differentiated learning that is effective and practical to use in learning. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study consisted of 18 grade IV students. Data collection methods include observation, interviews, questionnaires, and tests. The instruments used are instrument sheets and multiple-choice tests. Data analysis techniques use qualitative and quantitative descriptive analysis. The results of the study showed that the significance value (2-tailed) was 0.000. These results indicate that the significance value is less than 0.05 (p <0.05), so HO is rejected and Ha is accepted. Thus, it means that there is a significant difference in student learning outcomes in fraction material in mathematics before and after using interactive PowerPoint media. The implication of this study is that differentiation-based interactive PowerPoint media can be an alternative adaptive learning solution, as well as supporting the implementation of the Independent Curriculum more optimally in heterogeneous classes.